Global rogues and regional orders : the multidimensional challenge of North Korea and Iran - Cho, Il Hyun (New York : Oxford University Press, 2015)
A recent National Security Strategy report singles out nuclear proliferation as one of the gravest threats to the United States. Much of this fear is focused on North Korea and Iran, two'rogue states' that have violated nonproliferation rules and engaged in provocative actions, including nuclear and ballistic missile tests. Conventional wisdom dictates that the regimes in these countries have a uniquely defiant and dangerous nature, and that coercive measures such as sanctions and preemptive strikes are the most effective way to deal with them. But how do the neighbours of these two states view them, and how does this perception map onto the regional landscape in East Asia and the Middle East?
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on October 14, 2015).
Keywords: Nuclear nonproliferation -- Korea (North); Nuclear nonproliferation -- Iran; Nuclear nonproliferation -- Middle East; Nuclear nonproliferation -- East Asia; Regionalism; Security, International; United States -- Foreign relations -- East Asia; United States -- Foreign relations -- Middle East